Movement Disorders and Other Motor Abnormalities in Adults With 22q11.2 Deletion Syndrome - Boot, Erik (Am J Med Genet A, 2015)
Movement abnormalities are frequently reported in children with 22q11.2 deletion syndrome (22q11.2DS), but knowledge in this area is scarce in the increasing adult population. We report on five individuals illustrative of movement disorders and other motor abnormalities in adults with 22q11.2DS. In addition to an increased susceptibility to neuropsychiatric disorders, seizures, and early-onset Parkinson disease, the underlying brain dysfunction associated with 22q11.2DS may give rise to an increased vulnerability to multiple movement abnormalities, including those influenced by medications. Movement abnormalities may also be secondary to treatable endocrine diseases and congenital musculoskeletal abnormalities. We propose that movement abnormalities may be common in adults with 22q11.2DS and discuss the implications and challenges important to clinical practice.